2014
DOI: 10.4103/2319-4170.125651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental enrichment exposure on neuronal morphology of streptozotocin-induced diabetic and stressed rat hippocampus

Abstract: Background: Environmental enrichment (EE) exposure is known to influence the structural changes in the neuronal network of hippocampus. In the present study, we evaluated the effects of EE exposure on the streptozotocin (STZ)-induced diabetic and stressed rat hippocampus. Methods:Male albino rats of Wistar strain (4-5 weeks old) were grouped into normal control (NC), vehicle control (VC), diabetes (DI), diabetes + stress (DI + S), diabetes + EE (DI + E), and diabetes + stress + EE (DI + S + E) groups (n = 8 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Sections were further stained in 0.1% cresyl violet, dehydrated in 70% ethanol to 100% ethanol, cleared in xylene and mounted in DPX. Neuronal quantification was performed as described by Pamidi and Nayak (2014). The number of surviving neurons with their well-defined nuclei was counted while those with shrunken perikaryon and disintegrated nuclei were disqualified from quantification.…”
Section: Nissl Staining and Neuronal Quantificationmentioning
confidence: 99%
“…Sections were further stained in 0.1% cresyl violet, dehydrated in 70% ethanol to 100% ethanol, cleared in xylene and mounted in DPX. Neuronal quantification was performed as described by Pamidi and Nayak (2014). The number of surviving neurons with their well-defined nuclei was counted while those with shrunken perikaryon and disintegrated nuclei were disqualified from quantification.…”
Section: Nissl Staining and Neuronal Quantificationmentioning
confidence: 99%
“…We have shown that both regular and F I G U R E 3 Comparing H2O2 levels between the groups using one-way ANOVA. *Significant difference between C, RWD, and CWD groups with D group (p = .002, p = .002, and p = .003, respectively) Accordingly, Pamidi and Nayak (2014) reported that 30 days after injecting STZ, the number of survived hippocampal neurons were significantly decreased compared to that of the control group (Pamidi & Nayak, 2014 production and oxidative stress through activating NADPH oxidase (Zabielski et al, 2016). Prominently, oxidative stress and inflammation have been shown to be linked to high production of adhesion molecules and pro-inflammatory cytokines such as IL-6 and TNF-α, and thereby increasing the risk of diabetes.…”
Section: Discussionmentioning
confidence: 84%
“…Accordingly, Pamidi and Nayak (2014) reported that 30 days after injecting STZ, the number of survived hippocampal neurons were significantly decreased compared to that of the control group (Pamidi & Nayak, 2014). They have shown that the increased levels of apoptosis observed in experimental diabetes mellitus models are directly associated with the levels of free radicals and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, both EE and SE induce recovery in various models of central nervous system injury (Berrocal et al, 2007; Gajhede Gram et al, 2015; Lajud et al, 2018). Moreover, EE increases AHN in mouse models of Down syndrome (Chakrabarti et al, 2011; Pons-Espinal et al, 2013), Alzheimer’s disease (Levi and Michaelson, 2007; Mirochnic et al, 2009; Rodriguez et al, 2011; Valero et al, 2011; Llorens-Martin et al, 2013; Marlatt et al, 2013), Huntington’s disease (Lazic et al, 2006), diabetes (Pamidi and Nayak, 2014), ischemia (Rojas et al, 2013), and chronic pain (Zheng et al, 2017), after cranial irradiation (Garbugino et al, 2016), and during physiological aging (Kempermann et al, 1998, 2002; Kempermann, 2008, 2015; Speisman et al, 2013). In contrast, early SE reverses social deficits in animal models of autism (Garbugino et al, 2016; Campolongo et al, 2018), Parkinson’s disease (Goldberg et al, 2012), and Fragile X syndrome (Oddi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%